Implementation of the Online Population Administration Service System (SILAMO) Policy in Sumbawa District, Sumbawa Regency - Shafitri, Wendhi; Yamin, Ahmad; Dewi, Gheatriana (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
SILAMO is an application-based website which was created by the Population and Civil Registration Service of Sumbawa Regency with the aim of making it easier for the community to manage population administration, the services of which can only be carried out at the local village head/village office. The aims of this research are: 1) To describe the implementation of the online population administration service system (SILAMO) policy in Sumbawa District, Sumbawa Regency. 2) To describe the supporting and inhibiting factors for implementing the online population administration service system (SILAMO) policy in Sumbawa District, Sumbawa Regency. This research uses descriptive research with a qualitative approach, data collection techniques through interviews, observation and documentation, with key informants such as the Head of the population data sub-division of the Population and Civil Registry Service of Sumbawa Regency, the Secretary of the Pekat Village Head, the Pekat Village Head's government section, the Online Population Administration Operator SILAMO and the Community service recipient. The research results showed that the implementation of the Online Population Administration Service System (SILAMO) policy in Sumbawa District, Sumbawa Regency was carried out in two ways, namely a) Implementation of the policy according to George Edward III's theory, namely: Communication, Resources, Disposition and Bureaucratic Structure; b) Online population administration service standards which include: 1) service procedures, 2) completion time, 3) service costs, 4) service products, 5) facilities and infrastructure, 6) competence of service providers. Thus, it can be concluded that the implementation of the Online Population Administration Service System (SILAMO) policy in Sumbawa District, Sumbawa Regency was completed using two approaches, namely the implementation of service policies and online population administration service standards. The advice given is to speed up regulations and prepare human resources to support online population administration services.